FOREIGN EXPERIENCE IN DESIGNING MULTIFUNCTIONAL SPORTS CENTERS - Rode, Viktoriia; Kostiuchenko, Olha (Theory and practice of design, 2023)
The article researches the existing global practice of designing multifunctional sports centers. The question of the development of modern multifunctional sports centers in Ukraine is considered. Purpose. To substantiate and determine trends in the development of the architecture of sports facilities, as well as their multifunctional purpose; consider the world practice of designing sports facilities; conduct a comparative analysis of methods, techniques and technologies, as well as construction materials used in the construction of sports facilities in Europe with a similar solution in Ukraine. Methodology. The analysis of literary sources and foreign experience is used as research methods to justify the results. Results. The research results showed the following basic principles of designing sports centers: integration with the natural environment. use of the latest technologies, flexible use of space, specialized sports facilities for certain sports. A comparative analysis of methods, methods and technologies, as well as construction materials used in the construction of sports facilities in Europe with a similar solution in Ukraine, was conducted. The scientific novelty of this research lies in the comprehensive analysis and formation of multifunctional sports centers, as well as their impact on the environment. The study covers not only architectural components, but also innovative methods of using interactive technologies. Practical relevance. Understanding the basic principles of designing multifunctional sports centers can be used in the practical activities of designers and leisure organizations, which will allow to introduce creative ideas and effective means of creating a harmonious environment in their design.